Identifying the science and technology dimensions of emerging public policy issues through horizon scanning - Parker, Miles; Acland, Andrew; Armstrong, Harry J.; Bellingham, Jim R.; Bland, Jessica; Bodmer, Helen C.; Burall, Simon; Castell, Sarah; Chilvers, Jason; Cleevely, David D.; Cope, David; Costanzo, Lucia; et al. (Public Library of Science (PLoS), 2014)
Public policy requires public support, which in turn implies a need to enable the public not just to understand policy but also to be engaged in its development. Where complex science and technology issues are involved in policy making, this takes time, so it is important to identify emerging issues of this type and prepare engagement plans. In our horizon scanning exercise, we used a modified Delphi technique [1]. A wide group of people with interests in the science and policy interface (drawn from policy makers, policy adviser, practitioners, the private sector and academics) elicited a long list of emergent policy issues in which science and technology would feature strongly and which would also necessitate public engagement as policies are developed. This was then refined to a short list of top priorities for policy makers. Thirty issues were identified within broad areas of business and technology; energy and environment; government, politics and education; health, healthcare, population and aging; information, communication, infrastructure and transport; and public safety and national security.